Repositório Institucional da UFRN e Sistema Integrado de Gestão de Atividades Acadêmicas (SIGAA): proposta de interoperabilidade - Marques, Clediane de Araújo Guedes (2017)
Interoperability enables communication between open access digital repositories and can facilitate and expedite the production's deposit in repositories. In this context, from observation of duplicity of the scientific production stored in the Institutional Repository and in the integrated management system of academic activities, both at the Federal University of Rio Grande do Norte, and the absence of communication between the systems, the goal is to promote interoperability between these two systems with a view to print visibility to scientific production of members of the institution. With it, it broke the hypothesis that it is possible to make interoperable systems. The methodology used corresponds to action research, which provides joint actions between the researcher and participants. The research sample was composed of participants directly involved with the systems, aiming at a systematic collection of data. In this perspective, such systems were analyzed, through participant observation, as well as interviews with the respective were effective managers, and conducted the focus group, with some subjects of research. The content analysis was used to categorize and treat the inferences and generate the results. In this way, the research demonstrated that, of the various types of documents stored in the integrated management system of academic activities, only the dissertations and theses have prerequisites that contribute to interoperability. It is suggested that basis, actions and a model that aim to promote such interoperability.